Incidence of Respiratory Distress Syndrome and Its Associated Factors among Preterm Neonates: Study from West Java Tertiary Hospital - Irman Permana; Raden Tina Dewi Judistiani; Bakhtiar Bakhtiar; Ayu Alia; Tetty Yuniati; Budi Setiabudiawan (The Faculty of Veterinary Medicine of Syiah Kuala University, 2022)
Respiratory distress syndrome (RDS) or hyaline membrane disease is the most frequent cause of respiratory failure and mortality in preterm infants. As a result, many infants are brought to a neonatal intensive care unit (NICU). There may also be other factors that affect the incidence rate of RDS as well. Our research goals are to find out the incidence rate of RDS among three preterm groups and its related factors. In a cross-sectional-descriptive analytical study, newborn data was gathered and assessed by using hospital medical records. One hundred forty-two preterm infants with gestational age ≤ 36 weeks were hospitalized in the NICU. All participants were divided into three groups: extremely preterm ( 28 weeks), very preterm (28 to 32 weeks), and moderate-to-late preterm (32 to 36 weeks). The frequency of RDS and some related factors were compared among three groups. Finally, we analyzed the relationship between variables by SPSS statistics software version 19. The level of significance was considered P 0.05. Respiratory distress syndrome was observed in 64.68% of all participants; RDS is more common in infants within 28-32 weeks of gestation (81%), while infants with 28 weeks of gestation and 33-36 weeks of gestation have lower rates (50% and 52 Our study shows a positive correlation between birthweight and RDS as well as between birthweight and gestational age. (P value: 0.001, 0.003). Infants between 28 to 32 gestational age have a higher risk of RDS. The risk of RDS also increases in low birth weight and male infants.